Innovative Tissue‐Engineered Strategies for Osteochondral Defect Repair and Regeneration: Current Progress and Challenges. Issue 23 (26th October 2020) - Zhou, Liangbin; GJVM, Van Osch; Malda, Jos; Stoddart, Martin J.; Lai, Yuxiao; Richards, R. Geoff; Ki‐wai Ho, Kevin; Qin, Ling
Abstract: Clinical treatments for the repair of osteochondral defects (OCD) are merely palliative, not completely curative, and thus enormously unfulfilled challenges. With the in‐depth studies of biology, medicine, materials, and engineering technology, the conception of OCD repair and regeneration should be renewed. During the past decades, many innovative tissue‐engineered approaches for repairing and regenerating damaged osteochondral units have been widely explored. Various scaffold‐free and scaffold‐based strategies, such as monophasic, biphasic, and currently fabricated multiphasic and gradient architectures have been proposed and evaluated. Meanwhile, progenitor cells and tissue‐specific cells have also been intensively investigated in vivo as well as ex vivo. Concerning bioactive factors and drugs, they have been combined with scaffolds and/or living cells, and even released in a spatiotemporally controlled manner. Although tremendous progress has been achieved, further research and development (R&D) is needed to convert preclinical outcomes into clinical applications. Here, the osteochondral unit structure, its defect classifications, and diagnosis are summarized. Commonly used clinical reparative techniques, tissue‐engineered strategies, emerging 3D‐bioprinting technologies, and the status of their clinical applications are discussed. Existing challenges to translation are also discussed and potential solutions for future R&D directions are proposed. Abstract : Nowadays, many innovative tissue‐engineered approaches emerge for repairing and regenerating osteochondral defects (OCD). Various scaffold‐free and scaffold‐based strategies (e.g., monophasic, biphasic, multi‐phasic, and gradient architectures), engineered cells, bioactive factors, and drugs are widely investigated. Although tremendous progress is achieved, further research and development (R&D) is needed to convert preclinical outcomes into clinical applications.